Enhancing English Vocabulary Acquisition in Reading Instruction Through Multiple Intelligences Approach - Miolo, Sartin; Pilongo, Jolanda Hulda Deborah; Sambouw, Elsje L; Luwiti, Sri Rumiyati Ningsih (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2023)
This research explores innovative strategies to improve students' vocabulary mastery in English language teaching. Utilizing cognitive skill-based approaches, such as the "working with words" strategy, the study aims to create an effective and engaging learning environment. The research employs various methods, including observations, document analysis, recordings, and treatment procedures. Initial observations indicate that students possess a reasonable level of cognitive skills, providing a foundation for vocabulary acquisition. However, subsequent assessments reveal a decline in vocabulary proficiency, prompting the need for intervention. To address this issue, cognitive skill-based strategies, such as the "category game" and "contextual reading clues," are applied in the teaching process. These strategies aim to tap into students' intellectual capacities, motivating independent learning. Post-treatment results show significant improvement, with the contextual reading clues strategy leading to a remarkable 91.30% increase in vocabulary proficiency. In conclusion, cognitive skill-based strategies have a substantial impact on students' cognitive behaviors and vocabulary acquisition. This research emphasizes the importance of integrating vocabulary learning with reading exercises, continuous assessment, and progress recording. It underscores the significance of vocabulary mastery for language proficiency and calls for the integration of such strategies into language teaching practices.